Mortality Comparison of Using Anti Interleukin-6 Therapy and Using Standard Treatment in Severe Covid-19 - Sutadji, Jonathan Christianto; Widodo, Agung Dwi Wahyu; Indiastuti, Danti Nur (Folia Medica Indonesiana, 2021)
Severe Coronavirus Disease 19 (COVID-19) can cause serious lung inflammation and death. COVID-19 is characterized by a high mortality rate. This severity is associated with the overproduction of proinflammatory cytokines called "cytokine storms". One of the cytokines that play a central role is Interleukin-6 (IL-6). High IL-6 levels are associated with mortality. Expectedly, the IL-6 blockade could reduce cytokine storms and thus reduce deaths in severe COVID-19 patients. This systematic review aimed to summarize the comparison between mortality using anti-IL-6 therapy and mortality using standard treatment in severe COVID-19 patients. We systematically searched the PubMed, ScienceDirect, and ProQuest databases until 13 August 2020. After screening, twelve studies matched the inclusion criteria. The mortality of the anti-IL-6 therapy group was lower than the standard treatment group without anti-IL-6 therapy in COVID-19 patients in 10 of the 12 studies obtained. Four of the ten studies statistically found a significant difference in mortality of the anti-IL-6 therapy group and the standard treatment group. Confirmation of anti-IL-6 therapy effectiveness in reducing mortality in severe COVID-19 patients will require randomized controlled trials.